Róger Bolaños (1931–2007) - Gutiérrez, José María (2007)
This obituary highlights the life and scientific legacy of Róger Bolaños Herrera (1931–2007), a Costa Rican microbiologist and one of the founders of Instituto Clodomiro Picado. The text outlines his contributions to the development of antivenoms, his leadership in establishing research and training programs, and his role in promoting public health initiatives related to snakebite envenomation in Costa Rica and Central America.